The effects of technology and innovation adoption on firm performance among small and medium enterprises: Evidence from Vietnam’s logistics sector - Nguyen Thanh Tuan; Bekrar Abdelghani; Le Thi Muoi; Artiba Abdelhakim; Chargui Tarik; Vo Thi Le Hoa; Trinh Thi Thu Huong (Economics and Business Review)
In Industry 4.0, technology and innovation constitute a driver for enhancing firms’ performance, particularly for small and medium-sized enterprises (SMEs). Our study aims to examine whether that statement is correct for SMEs in a developing country. We developed a generic model and employed multiple regression techniques, including ordinary least-squares, robust standard errors and weighted least squares, to test this hypothesis and address heteroskedasticity. Using a micro-level dataset including 11,630 SMEs in Vietnam’s logistics sector, an emerging logistics market in a developing country, our results reveals that the effects of technology on firm performance may differ depending on particular metrics of this performance. Furthermore, not all forms of innovation significantly affect SME performance. Control variables such as “firm’s age”, “firm’s size”, “state ownership”, “education of the manager” and “foreign activities” also play a significant role in SME performance, underscoring the importance of both internal capabilities and external technological elements.